What Comprises a Successful Educational Science YouTube Video? A Five-Thousand User Survey on Viewing Behaviors and Self-Perceived Importance of Various Variables Controlled by Content Creators - Beautemps, Jacob; Bresges, André (Frontiers in Communication, 2021)
Educational videos on digital platforms are an attractive source of learning, especially for the young generation, as they provide easy, personalizable access to a wide variety of learning content. Allowing for simplified explanations and visual demonstrations, educational videos are highly suitable for scientific content. With 400 hours of video content uploaded per second, YouTube is the most used video platform with user-generated content worldwide. This study provides an initial insight into what elements influence the perceived quality of educational science videos by viewers. In response to a call for study participants via various German science YouTube and Instagram channels, over 5.000 participants between the ages 9 to 72 (M = 18, SD = 8,78) completed a web questionnaire on their viewing behaviors and self-perceived importance of various variables controlled by content creators. Six key elements which make for a successful YouTube video were identified: 1) structure, 2) reliability, 3) quality, 4) community integration, 5) presenter, 6) topic. Based on these elements, a catalogue with 17 recommendations for the creation of successful educational videos was developed, serving as a practical guideline for content creators.